Geolocating the stranger: the mapping of uncertainty as a configuration of matching and warranting techniques in dating apps. Issue 3 (3rd September 2018) - Veel, Kristin; Thylstrup, Nanna Bonde
ABSTRACT: Geolocation as an increasingly common technique in dating apps is often portrayed as a way of configuring uncertainty that facilitates playful interaction with unknown strangers while avoiding subjecting the user to unwanted risks. Geolocation features are used in these apps on the one hand as matching techniques that created links between the user and potential partners through geographical location, and on the other as warranting techniques that can help a user to determine whether to trust a given profile. Tracing a trajectory from Georg Simmel's figure of the stranger as intrinsic to modern urban culture, through Stanley Milgram's familiar stranger as an inspiration for the infrastructure of social networking sites, to a consideration of the double perspective of overview and embedment inherent in geolocation's ability to map, we identify the stalker as an emblematic figure that appears not as a threatening Other, but rather as our own doubling.